Digital and innovation skills in health care professionals in Europe. (30th September 2020) - Fornes-Romero, G; Doñate-Martinez, A; Garces-Ferrer, J; Fredskild, T U; Hansen, H; Traver-Salcedo, V; Martinez-Piqueras, M; Gil-Granados, A; Gimenez-Campos, S
Abstract: Background: Rising life expectancy and ageing population are current phenomena that European society is facing and these are challenges for the European healthcare systems. To face them, several e-health solutions are already designed to optimize resources of the healthcare provider system. However, most of them are not being implemented or deployed. Some of the reasons are the lack of digital skills and innovation readiness in staff, and existing barriers to changing organizational practices. Objectives: The DISH project (601008-EPP-1-2018-1-DK-EPPKA2-SSA) will develop 3 concepts to improve the digitalization of healthcare staff to help them in the use of e-health solutions already developed: 1)Learning Innovation Units, where healthcare staff, SMEs and educational institutions work together for improving the e-health solutions development and implementation; 2)On the job training, where healthcare staff will be trained in e-health and digital competences; 3)Assessment, where competences accomplished by healthcare staff will be recognized. All these concepts will be tested in 6 EU countries. Results: The development of the 3 concepts is based on a needs analysis on present and future competences required to support the implementation of e-health solutions in Denmark, Norway, UK, Germany, Spain and Poland. Also, each country will test the 3 concepts and train 100 healthcare staff in the use of an e-solution/innovation already developed but not being fully implemented. An evaluation of the achieved skills/competences by the staff will be also conducted. Conclusions: Healthcare workers and SMEs show willingness and motivation in contributing to the digitalization but there is a clear lack of digital skills (although this is different from country to country) to make easier the adoption in daily practice of such solutions. The project looks for promoting close collaboration between the interested parties to work together in overcoming the stated deficiency. Key messages: The DISH concepts will facilitate a training framework for healthcare professionals in the use of digital solutions. The DISH project will promote the use of several innovations already available in the market.